PENGARUH STUDENT SATISFACTION TERHADAP COMPETITIVE ADVANTAGE DENGAN UNIVERSITY REPUTATION DAN STUDENT LOYALTY SEBAGAI VARIABEL INTERVENING - Budiman Chan (Business Accounting Review, 2015)
This Study aimed to examine the affect of student’s satisfaction to competitive advantage with university reputation and student’s loyalty as the mediators. The data that used in this study were primary data. This study used students from 6 private universities in Surabaya as samples with purposive sampling method. The hypotheses in this study was analyzed by using Partial Least Square method. The result from this study showed a direct impact of positive and significant of the student’s satisfaction to competitive advantage, but the university reputation and student’s loyalty cannot become as the mediators.